Molecular Investigation of the Transmission Pattern of Brucella suis 3 From Inner Mongolia, China - Liu, Zhi-guo; Wang, Li-jun; Piao, Dong-ri; Wang, Miao; Liu, Ri-hong; Zhao, Hong-yan; Cui, Bu-yun; Jiang, Hai (Frontiers in Veterinary Science, 2018)
Brucellosis is an endemic disease in China affecting both humans and livestock. The aim of the present study was to analyze two Brucella strains isolated from sheep spleen from Ulanqab in Inner Mongolia, China using classical biotyping and molecular typing. The two strains were determined to be B. suis biovar 3 and were closely related to isolates that were previously obtained from two different hosts (human and swine) in Guangxi Province. Our results suggest that B. suis can be directly or indirectly transferred from swine to sheep, and these animals act as reservoirs for B. suis infection, which can be transferred to humans. Multiple Locus Variable-number tandem repeat Analysis (MLVA) is a useful tool for tracing the geographical origin of brucellosis infections and elucidating its transmission patterns.